Sex
1 online resource (232 pages).
Keywords: Focusing on the unacknowledged, personal and often unconscious dimension, Sex explores the intersection between sex and ethnography. Anthropological writing tends to focus on the influence of status markers such as position, gender, ethnicity, and age on fieldwork. By contrast, far less attention has been paid to how sex, sexuality, eroticism, desire, attraction, and rejection affect ethnographic research. In the book, anthropologists reflect on their own encounters with sex during fieldwork, revealing how attraction and desire influence the choice of fieldwork subjects, field sites and friendships. They also examine the resulting impact on fieldwork findings and the generation of knowledge. Based on fieldwork in Germany, Denmark, Greece, the USA, Brazil, South Africa, Singapore, Turkey, Israel, Morocco, and India, the contributors go beyond the common heterosexuality/homosexuality divide to address topics which include celibacy, polyamory and sadomasochism. This long overdue text provides perspectives from a new generation of anthropologists and brings the debate into the 21st century. Examining challenging and controversial issues in contemporary fieldwork, this is essential reading for students in anthropology, gender and sexuality studies, sociology, research methods, and ethics courses.